Female black flies of simulium (diptera: simuliidae) collected on humans in Tam Dao National Park, Vietnam: Description of a new species and notes on four species newly recorded from Vietnam - Takaoka, H.; Sofian-Azirun, Mohd; Ya'cob, Z.; Chen, C.D.; Lau, K.W.; Pham, H.T. (The Malaysian Society of Parasitology and Tropical Medicine, 2014)
A total of 29 female black flies were captured by a hand net as they swarmed around humans in Tam Dao National Park, Vinh Phuc Province, Vietnam. They included one species of the subgenus Gomphostilbia (Simulium (Gomphostilbia) asakoae Takaoka & Davies) and five species of the subgenus Simulium, of which one species is described as Simulium (Simulium) vietnamense sp. nov. and the other four species (S. (S.) chungi Takaoka & Huang, S. (S.) grossifilum Takaoka & Davies, S. (S.) maenoi Takaoka & Choochote, and S. (S.) rufibasis Brunetti) are newly recorded from Vietnam.